Cardiovascular Disease Risk Factors and Platelet Mitochondrial Function in School Age Children (P21-059-19). (13th June 2019) - Fuentes, Eva Diaz; Adams, Sean; Young, Catarina; Weber, Judith; Borsheim, Elisabet
Abstract: Objectives: Platelets (PL) are an accessible source of human mitochondria. Thus, PL are advantageous when studying mitochondrial function in vulnerable populations. The objective of this study was to measure the association between parameters of PL mitochondrial respiration and markers of cardiovascular disease risk [adiposity, fitness and blood pressure (BP)] in a sub-sample of school age children participants of a larger study called Arkansas Active Kids. Methods: After overnight fasting, body composition (DXA), VO2peak (incremental cycle ergometer test), resting BP, and mitochondrial function of permeabilized platelets (high-resolution respirometry) were measured in 46 children. Routine respiration (R), fatty acid oxidation (F = octanoylcarnitine + ADP + malate), respiratory stimulation by simultaneous action of F plus NADH-linked complex (C) I substrates (F&CI = pyruvate, malate and glutamate), succinate (F&CI&CII), and glycerolphosphate (F&CI&CII&GpDH) were measured. Noncoupled electron transfer capacity (ETE, FCCP), CIIE &GpDHE respiration (rotenone), residual oxygen consumption (ROX, antimycin) and CIV activity were also measured. Flux control ratios were computed by normalizing to ET capacity in the presence of NADH-linked substrates. Data presented as mean ± SD and Spearman correlations (Rho). Results: Children were 9 ± 1 years with an average BMI percentile (BMIp ) of 59 ± 30, and % fat mass (%FM) of 33 ± 6% (range: 25 to 49%). Ten children (22%) had either elevated or stage 1 hypertension as defined by the American Academy of Pediatrics. Diastolic BP percentile, VO2peak (ml·kg −1 fat-free-mass −1 ), BMIP, and % fat mass (%FM) did not correlate with any parameter of platelet mitochondrial respiration. However, visceral fat area (cm 2 ) correlated with FAO (Rho = 0.35, P  = 0.017) and F&CI (Rho = 0.30, P  = 0.043) while systolic BP correlated with F&CI&CII&GpDH (Rho = 0.31, P  = 0.037) and ETE (Rho = 0.43, P  = 0.003). Conclusions: In this preliminary analysis, PL fatty acid oxidation of school-age children increased with increasing visceral adiposity while the convergent electron flow through the Q-junction increased with increasing systolic blood pressure. Funding Sources: USDA 59-6250-4-001; NIH P20GM109096. USDA/ARS Project 6026-51000-010-05S.